Location awareness in managing business of Petronas Trading Corporation Sdn. Bhd. (PETCO) / Shazrizana Rosli - Rosli, Shazrizana (2011)
Location factors are very important to many organizations. A good location factor may promise a good feedback from the customers or even the supplier towards the products and services offered. This project paper is to assess Location factors strategies that PETRONAS= Trading Corporation Sdn. Bhd. managed to make a business with other countries. The objective of this research is to investigate the level awareness of location such as political, economic, societal, technological and legal that PETRONAS Trading Corporation Sdn. Bhd. dealing with. The research title “Location Awareness in Managing Business of PETRONAS Trading Corporation Sdn. Bhd. (PETCO) had been conducted to obtain the results at PETRONAS Trading Corporation Sdn. Bhd. (PETCO). This research has been answered by 56 respondents through questionnaire. The data had been analyzed by using Statically Package for Social Science (SPSS) version 17.0 has been used to summarize the data. Based on this research, the results indicates that political and technological are the elements that contribute most in location awareness. As a conclusion, the results of the findings from the analysis shows that political and technological factors influence the location awareness in managing a business towards PETRONAS Trading Corporation Sdn. Bhd. (PETCO). Thus, recommendation is included in this project paper, in order to help PETRONAS Trading Corporation Sdn. Bhd. to increase the level of location awareness in managing business strategies and reduce the risk of the company’s revenue.